SURVEY OF MEDICAL STUDENTS' INTEREST IN CONTINUING THEIR EDUCATION IN KABUL, 2021-2022 - Murtaza Jafari; Abdulbasit Taib; Palwasha Rahmani (Scholar Express Journals, 2022)
Science and knowledge is the main way for humans to improve their lifestyle and ease of life. In general, all countries are trying to play an important role in creating a stable country by providing appropriate and excellent educational services, in which the young generation has an important and key role. The young generation with education can be a source of service in their society, however due to some problems in society, it causes the interest to continue education in the capable class of society to decrease. Objectives of the Research: The main purpose of this research is to examine and determine the level of interest in continuing education among medical students in Kabul and the important factors in making this decision. Research Method: This research is a cross-sectional descriptive, prospective study in which a questionnaire prepared in medical educational institutions in Kabul was distributed during the six months of 2021 and 2022, and after collecting data, the results were reviewed
Keywords: interest in education; medical students and Kabul city; addressed; interest